A Four-Months-Neglected Anterior Shoulder Dislocation Treated with Open Reduction and Internal Fixation: A Case Report - Andika Prasetyo Arifin; Sammy Saleh Al Huraiby (Yayasan Literasi Sains Indonesia, 2026)
Neglected anterior shoulder dislocation (NASD) is an uncommon yet clinically demanding condition, largely because diagnosis and treatment are frequently delayed. Patients often develop secondary problems such as glenoid bone loss, capsular contracture, and ongoing instability, all of which call for a carefully chosen surgical strategy. This report describes the management of a chronic case using open reduction and internal fixation. A 25-year-old man was seen after sustaining an anterior shoulder dislocation that had remained untreated for four months. Clinical examination combined with plain radiographs established the diagnosis. Through a deltopectoral approach the glenohumeral joint was reduced under direct vision and stabilized with two 2.0-mm K-wires. At the two-week review both clinical examination and repeat radiographs confirmed that the joint had been restored to an anatomic position with good stability. The patient had no appreciable sensory or motor deficit in the limb, and neurovascular function remained intact. These early results indicate that open reduction and internal fixation can reliably address chronic NASD and reduce the risk of recurrent instability. Nevertheless, longer-term surveillance is required to confirm lasting joint stability and to detect any late complications that may develop.